Pancreatic traumatisms: statistical study - Cassinelli, Daniel; Armand Ugon, Alfredo; Dapueto, Loreley; Baglivi, Nicolás (Cirugía del Uruguay, 1980)
The authors study a series of 23 cases of pancreatic lesions between the years 1969 and 1979. This is compared to a former series of 1 7 cases covering up to 1969. This evaluation covers frequency, lesional types, therapy and results in their respective percentages, and morbi - mortality is compared. There follows a series of conclusions.